Implementation of Customer Engagement at PT. Bank Danamon Tbk, Makassar Branch Slamet Riyadi - Verawaty Verawaty; Azis Azis (Jurnal Economic Resource, 2023)
The purpose of the study was to analyze the application of customer engagement at PT Bank Danamon Indonesia Tbk Makassar Branch Slamet Riyadi. The research method used in this study is qualitative research which can also be called explanatory research. The data collection technique used is an interview technique, by randomly interviewing customers related to four indicators in the application of customer engagement, including CLV, CRV, CIV, and CKV. The number of informants interviewed was four. The results showed that CLV (Customer Lifetime Value) runs well, as evidenced by the commitment from customers to continue using the products offered by PT Bank Danamon Tbk Makassar Branch Slamet Riyadi because of the good service and the information provided by management / employees is very clear and easy to understand. CRV (Customer Referral Value) and CIV (Customer Influencer Value) of old customers have acted as good marketers in delivering Bank Danamon products, services, and services to potential customers, even though the dissemination of Bank Danamon by customers has not been done through social media only word of mouth. CKV (Customer Knowledge Value) customers actively convey their suggestions and criticisms related to service, directly to top management, for customer products it has not been literate that the role of customers is very large to help Bank Danamon in making good and useful products for customers.